Identifikasi Molekuler Jamur Trichoderma Sp. Endofitik Pada Tanaman Padi - Herfandi Lamdo; Nabillah Anissa; Damsir Damsir (JURNAL WACANA PERTANIAN, 2023)
Endophytic fungi are types of microorganisms that live in healthy plant tissues without causing symptoms or damage to the host (Tayung & Jha, 2010; Aly et al., 2010). One of the most common endophytic fungi capable of acting as biological control agents is Trichoderma sp. Trichoderma sp. can suppress disease-causing pathogens in plants, especially soil-borne pathogens through mycoparasitism, competition and antibiosis mechanisms and can also directly stimulate plant growth and stimulate disease resistance responses (Widyastuti & Hariani, 2006; Soesanto et al., 2011). This study aims to identify Trichoderma sp. endophytic roots of rice plants to be used as biological control agents in tomato plants infected with Tobacco Mosaic Virus. This research was conducted at the Laboratory of Agrtochnology Satu Nusa Lampung University and PT Genetics Science Indonesia from September to December 2022. Endophytic Trichoderma sp isolates on rice plant roots that have been identified molecularly include Trichoderma asperellum species with analysis results. that the percentage of similarity is very high and the max score is above 700 and the e-value is 0.0.